PENERAPAN METODE PEMBELAJARAN SQ3R (SURVEY, QUESTION, READ, RECITE, AND REVIEW) DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs AL- MU’MIN DOGANG - Windi Khairun Nisa; Yunus Ismail; Khairuddin YM (Jurnal Iqtirahaat, 2023)
T This study used the Classroom Action Research (CAR) method with the object being class VIII students at MTs Al-Mu'min Dogang. Data collection techniques in this study were observation, interviews and written and unwritten tests. This research is more in the nature of solving a problem whose results are described as a whole. The results of this study indicate that 1) in the first cycle, 19 students achieved completeness and 11 students who did not complete with an average score of 73.1. Whereas in cycle II there were 28 students who completed and 2 students who did not complete with an average score of 77 using the SQ3R method (Survey, question, Read, Recite, and Review) can improve student learning outcomes in class VIII in the Islamic Cultural History subject . Then it can be concluded that what the researcher wants can be said to be successful and the cycle is not continued. and Review) can improve student learning outcomes in class VIII Islamic Cultural History subjects. Then it can be concluded that what the researcher wants can be said to be successful and the cycle is not continued. and Review) can improve student learning outcomes in class VIII Islamic Cultural History subjects. Then it can be concluded that what the researcher wants can be said to be successful and the cycle is not continued